1990
DOI: 10.1182/blood.v75.4.1024.bloodjournal7541024
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate/severe acute graft-versus-host disease after allogeneic bone marrow transplantation: an analysis of clinical risk features and outcome

Abstract: We have analyzed the long term outcome of 197 patients who were treated for grade II to IV acute graft-versus-host disease (GVHD) following histocompatible allogeneic bone marrow transplantation (BMT). Of 469 recipients of sibling donor allografts performed at our center between January, 1979 and October, 1987, 197 patients (42%) developed greater than or equal to grade II acute GVHD at a median of 38 days (range 9 to 98 days) post-BMT. After treatment with corticosteroids (n = 160) or other immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 0 publications
5
48
0
1
Order By: Relevance
“…The outcome data from our report of tacrolimus and ATGAM therapy suggests superior response rates and survival than either agent alone. It also compares favourably with published data on the prognosis of GVHD after secondary therapy in which outcome is very poor (Deeg & Henslee-Downey, 1990;Weisdorf et al, 1990;Martin et al, 1991;Pavletic et al, 1999). Reports of newer monoclonal antibodies in the management of steroid refractory acute GVHD also detail promising response rates warranting further investigation (Heslop et al, 1995;Przepiorka et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The outcome data from our report of tacrolimus and ATGAM therapy suggests superior response rates and survival than either agent alone. It also compares favourably with published data on the prognosis of GVHD after secondary therapy in which outcome is very poor (Deeg & Henslee-Downey, 1990;Weisdorf et al, 1990;Martin et al, 1991;Pavletic et al, 1999). Reports of newer monoclonal antibodies in the management of steroid refractory acute GVHD also detail promising response rates warranting further investigation (Heslop et al, 1995;Przepiorka et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Preventative strategies with immunosuppressive agents have been extensively studied in randomized trials, with the combination of cyclosporine and short-course methotrexate being adopted as a common standard care (Storb et al, 1986(Storb et al, , 1989(Storb et al, , 1992Ringden et al, 1993). When acute GVHD occurs, high-dose glucocorticosteroids are the mainstay of treatment (Martin et al, 1990Weisdorf et al, 1990), with failure to respond associated with a very poor prognosis. Intensification of immunosuppression with anti-thymocyte globulin (ATGAM), monoclonal anti-T-cell antibodies, and anti-cytokine or anti-cytokine receptor monoclonal antibodies is an alternative option (Doney et al, 1981;Roy et al, 1992;Anasetti et al, 1994;Antin et al, 1994;Herbelin et al, 1994;Hebart et al, 1995).…”
mentioning
confidence: 99%
“…Moreover, the current survival at years in patients who respond to steroids is about 36% versus 17% in nonresponders (NR) [6] and it has been shown that transplantation-related mortality (TRM) is higher in steroidresistant patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many advances in haematopoietic cell transplantation (HCT), acute graft-versus-host disease (GVHD) remains a major cause of morbidity and mortality. Corticosteroids are the conventional first-line systemic therapy, but only 1/2 of patients will respond and only 1/3 will have a durable response (Weisdorf et al, 1990a;MacMillan et al, 2002a). It is well established that patients with severe (clinical grade III-IV) acute GVHD are less responsive to steroids leading to poor survival and high transplant-related mortality (TRM).…”
mentioning
confidence: 99%